2000
DOI: 10.1007/s001250050045
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone short-term monotherapy lowers fasting and post-prandial glucose in patients with Type II diabetes

Abstract: Because insulin resistance plays a prominent part in the development of Type II diabetes [1,2], therapeutic interventions to improve insulin action are likely to be of considerable benefit in the management of the condition. The thiazolidinediones (or glitazones) are a new class of orally active drugs that reduce insulin resistance [3] and hence increase glucose uptake in skeletal muscle and adipose tissue, as well as decrease hepatic glucose production. These effects are thought to be mediated through interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
115
4
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(134 citation statements)
references
References 21 publications
13
115
4
2
Order By: Relevance
“…Treatment with thiazolidinediones has resulted in either no significant reduction or, at best, a modest lowering of plasma TGs in clinical trials in humans with insulin resistance and Type 2 diabetes (31), despite their documented insulin sensitizing effects (21,32,33). This is consistent with our observation that treatment with rosiglitazone resulted in a non-significant reduction in fasting plasma TG levels in the fructose-fed hamster, an animal model of mild hypertriglyceridemia associated with VLDL oversecretion.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Treatment with thiazolidinediones has resulted in either no significant reduction or, at best, a modest lowering of plasma TGs in clinical trials in humans with insulin resistance and Type 2 diabetes (31), despite their documented insulin sensitizing effects (21,32,33). This is consistent with our observation that treatment with rosiglitazone resulted in a non-significant reduction in fasting plasma TG levels in the fructose-fed hamster, an animal model of mild hypertriglyceridemia associated with VLDL oversecretion.…”
Section: Discussionsupporting
confidence: 83%
“…This is consistent with the demonstration of increased whole-body glucose disposal rate with treatment of fructose-fed hamsters in the present study. Rosiglitazone treatment has also resulted in insulin sensitization of adipose tissue (20) and has often led to a reduction of plasma FFA levels and flux (21,22). Although rosiglitazone treatment did not result in a significant reduction in fasting plasma FFA in the present study, we cannot rule out that rosiglitazone treatment in this model may have resulted in lower postprandial FFA levels and lower overall FFA flux to the liver.…”
Section: Discussioncontrasting
confidence: 65%
“…Several clinical studies have suggested that glitazones may improve glycemic control, insulin sensitivity, and circulating lipid levels in type 2 diabetic patients (17)(18)(19). Troglitazone has also been shown to increase insulin sensitivity in subjects with impaired glucose tolerance (IGT) (20 -22) and women with polycystic ovary syndrome (23).…”
mentioning
confidence: 99%
“…These findings suggest that the effect of TZDs on biomarkers of cardiovascular risk may be independent of their antidiabetic actions. 129 Previous data indicate that throughout the spectrum of insulin resistance, from the metabolic syndrome to type 2 diabetes, PAI-1 levels are increased. 130 Because PAI-1 promotes clot formation in plasma and various studies demonstrated an association between circulating PAI-1 levels and cardiovascular events, 131 a TZD-mediated decrease in PAI-1 might play an important role in reducing the incidence of CAD and its complications in this population.…”
Section: Inflammation and Atherosclerosismentioning
confidence: 99%